THE EFFECTIVENESS OF THE SUGGESTOPEDIA METHOD IN IMPROVING POETRY WRITING SKILLS OF FIFTH-GRADE ELEMENTARY SCHOOL STUDENTS - Mardiana Norza; Amirul Mukminin Al Anwar; Tika Sari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Writing poetry is an important component of language learning in elementary schools because it allows students to express ideas, feelings, and experiences through written language. However, in reality, many students still experience difficulties in developing ideas, choosing appropriate diction, and constructing a coherent poem structure. These difficulties often impact students' low ability in poetry writing activities. Therefore, the purpose of this study was to determine how well fifth-grade elementary school students can use the Suggestopedia method to improve their poetry writing skills. This study used a two-cycle method called Classroom Action Research (CAR), which includes planning, implementation, observation, and reflection as the four phases of each cycle. Fifth-grade elementary school students participated in this study. Examinations of students' written work, classroom observations, and records of their academic progress were used to collect data. After using the Suggestopedia method, students' poetry writing skills improved significantly, according to the research findings. From 63.2 in the pre-action stage to 72.4 in Cycle I, and even better to 80.6 in Cycle II, the average score showed a significant increase. The level of student learning mastery also increased, from 36% in the pre-action stage to 56% in Cycle I and 84% in Cycle II.